Ensemble learning techniques for transmission quality classification in a Pay&Require multi-layer network - Żelasko, Dariusz; Pławiak, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
Due to a continuous increase in the use of computer networks, it has become important to ensure the quality of data transmission over the network. The key issue in the quality assurance is the translation of parameters describing transmission quality to a certain rating scale. This article presents a technique that allows assessing transmission quality parameters.
Keywords: Pay&Require; ensemble learning; machine learning; resource allocation; QoS